EFFECT OF INTERNAL CONTROL ON FRAUD PREVENTION IN EBONYI STATE MINISTRIES, DEPARTMENT AND AGENCIES (MDAs) - Nwite, Isaiah Michael; Uguru, Leonard C; Chukwu, Uche Christopher; Elom, Joseph O. (EBSU Journal of Social Sciences and Humanities, 2024)
This study examined the effect of internal control on fraud prevention in Ebonyi State Ministries Department and Agencies (MDAs). The main objective of this study is to determine the effect of internal control on fraud prevention in Ebonyi State Ministries, Department and Agencies (MDAs).Specifically the study sought to ascertain the effect of control activities on fraud prevention in Ebonyi State Ministries Department and Agencies (MDAs), to determine the effect of control environment on fraud Prevention in Ebonyi State Ministries Department and Agencies (MDAs) and to examine the effect of monitoring activities on fraud prevention in Ebonyi State Ministries Department and Agencies (MDAs). The study employed cross survey design and ordinary least square estimation technique complimented by statistical package for social sciences (SPSS) primary data was generated from the respondents using structured questionnaire. The study finding underline that control environment, control activities and monitoring activities has significant effect on fraud prevention in Ebonyi State Ministries Department and Agencies (MDAs). The study recommended that Ebonyi State Ministries Department and Agencies (MDAs) should ensure that an effective and adequate internal control system such as control environment, control activities and monitoring activities should be put in place since internal control system prevent fraud occurrences in the Ministries